Generation of 'designer erythroblasts' lacking one or more blood group systems from CRISPR/Cas9 gene‐edited human‐induced pluripotent stem cells. Issue 19 (21st September 2021) - Pandey, Priyanka; Zhang, Nanyan; Curtis, Brian R.; Newman, Peter J.; Denomme, Gregory A.
Abstract: Despite the recent advancements in transfusion medicine, red blood cell (RBC) alloimmunization remains a challenge for multiparous women and chronically transfused patients. At times, diagnostic laboratories depend on difficult‐to‐procure rare reagent RBCs for the identification of different alloantibodies in such subjects. We have addressed this issue by developing erythroblasts with custom phenotypes (Rh null, GPB null and Kx null/Kell low) using CRISPR/Cas9 gene‐editing of a human induced pluripotent stem cell (hiPSC) parent line (OT1‐1) for the blood group system genes: RHAG, GYPB and XK . Guide RNAs were cloned into Cas9‐puromycin expression vector and transfected into OT1‐1. Genotyping was performed to select puromycin‐resistant hiPSC KOs. CRISPR/Cas9 gene‐editing resulted in the successful generation of three KO lines, RHAG KO, GYPB KO and XK KO. The OT1‐1 cell line, as well as the three KO hiPSC lines, were differentiated into CD34 + CD41 + CD235ab + hematopoietic progenitor cells (HPCs) and subsequently to erythroblasts. Native OT1‐1 erythroblasts were positive for the expression of Rh, MNS, Kell and H blood group systems. Differentiation of RHAG KO, GYPB KO and XK KO resulted in the formation of Rh null, GPB null and Kx null/Kell low erythroblasts, respectively. OT1‐1 as well as the three KO erythroblasts remained positive for RBC markers—CD71 and BAND3. Erythroblasts were mostly at the polychromatic/ orthochromatic stage of differentiation. Up to ~400‐fold increase in erythroblasts derived from HPCs was observed. The availability of custom erythroblasts generated from CRISPR/Cas9 gene‐edited hiPSC should be a useful addition to the tools currently used for the detection of clinically important red cell alloantibodies.